Trends in family planning and counselling for women with sickle cell disease in the UK over two decades. Issue 2 (23rd May 2014) - Eissa, Asma A; Tuck, Susan M; Rantell, Khadija; Stott, Daniel
Abstract : Background: Pregnancies in women with sickle cell disease (SCD) are known to have high rates of maternal and fetal mortality and morbidity. Given these pregnancy-associated problems for women with SCD, advice both about pregnancy planning and about effective contraception are of paramount importance. This study sought to discover the contraception methods used by women with SCD, what complications women with SCD encounter with contraception, and their experiences of pre-pregnancy counselling and pregnancy planning, and how such issues may have changed over the past two decades. Method: The study was a multicentre, interview-based, cross-sectional study. Interviews were carried out with 102 women with SCD, in north and central London during 2010, concerning their current and previous contraceptive use, their pregnancy history, their menstrual history, and the advice they received concerning pregnancy planning and contraception. Patient information was anonymised and ethical approval was obtained. These data were compared with data from a similar study undertaken in 1993. Results: There were significant differences in a number of key areas: the number of unplanned pregnancies decreased from 64% in 1993 to 53% in 2010. The number of women with SCD who were advised not to become pregnant also fell, from 36% to 15%. The use of combined oral contraceptive pills declined, from 45% of the women in 1993 to 31% in 2010. Conversely the use of depot medroxyprogesterone acetate contraception (DMPA) and the levonorgestrel intrauterine system (LNG-IUS) both increased. Conclusions: Significant changes in the contraceptive methods used by women with SCD are demonstrated in the London population. LNG-IUS use in SCD has not been investigated before. There has been an encouraging decrease in the number of women with SCD who are advised not to become pregnant, perhaps reflecting an improvement in their overall health. Although the number of unplanned pregnancies has fallen, it remains high – emphasising the continuing need for women with SCD to have access to informed advice about pregnancy-associated issues and contraception.